Can graphene take part in the fight against COVID-19?. (August 2020) - Palmieri, V.; Papi, M.
Graphical abstract: Highlights: Functionalized graphene can capture viruses and deliver antiviral drugs. Viruses on graphene can be inactivated by light or heat treatments. Graphene can be used as coating material for medical devices, personal protective equipment or facemasks to minimize the risk of transmission. Graphene-based sensors can be embedded in textiles and environmental filters or used for high-throughput screening of virus helicase inhibitors. Abstract: The pneumonia outbreak of coronavirus disease 2019 (COVID-19) represents a global issue. The bidimensional material graphene has captured much attention due to promising antimicrobial applications and has also demonstrated antiviral efficacy. In response to this global outbreak, we summarized the current state of knowledge of graphene and virus interaction as well as possible successful applications to fight COVID-19. Antibody-conjugated graphene sheets can rapidly detect targeted virus proteins and can be useful for large population screening, but also for the development of environmental sensors and filters, given the low cost of graphene materials. Functionalized graphene has demonstrated a good viral capture capacity that, combined with heat or light-mediated inactivation, could be used as a disinfectant. Graphene sensors arrays can be implemented on standard utility textiles and drug efficacy screening. Thanks to its high versatility, we foresee that graphene may have a leading role in the fight against COVID-19.